091. Impact of the Covid-19 Pandemic on Breast Cancer Surgery Care in 8 Institutiona Around Southeast and South Asia - Sasongko Hadi Priyono; PW Nurikhwan (JBN (Jurnal Bedah Nasional))
Background: The COVID-19 pandemic brought about unprecedented disruptions to surgical services globally, which could have led to delays in surgical care for breast cancer patients. This study analysed the institutional responses of tertiary hospitals from selected Asian countries to the COVID-19 pandemic. Methods: We identified all patients newly diagnosed with breast cancer from 16 institutions (9 countries: Singapore, Bangladesh, India, Indonesia, Malaysia, Pakistan, Philippines, Sri Lanka and Vietnam) from 11 Mar 2020 to 10 Mar 2021 (“covid”) and compared them to those diagnosed 11 Mar 2019 to 10 Mar 2020 (“precovid”). The following data were collected and retrospectively analysed: number of breast cancer surgeries and timeliness of surgery (days from diagnosis to surgery); type of surgery (breast conserving surgery [BCS], mastectomy without [Ms] and with reconstruction [MRecon]), and clinical stage at diagnosis. Results: 4816 patients (2550 in “precovid” and 2266 in “covid” cohort) were included. Median age at diagnosis was 57 for both cohorts (r, 20-117) (p=0.79). In overall number of cases (n=4877), there is no statistically significant difference between pre- (n=2515, 51.6%) v. covid (n=2362, 48.4%) period (p=0.26). Sequence of treatments was similar in both cohorts (upfront surgery [n=3983 cases, 53.7% v. 46.3%, p=0.08; or surgery after neoadjuvant therapy [n=878 cases, 48.9% v. 51.1%, p=0.79]). Five of 16 institutions experienced a decrease in number of surgeries (p<0.05) during the first year of the pandemic, and across all 3 types of surgery, while 1 institution received more cases (p=0.002). Two other institutions had statistically significant more patients with neoadjuvant therapy (p=0.003 and p<0.001) and 1 of these two showed an increase in BCS (p=0.04) and MRecon (p=0.04) cases during covid compared to the precovid period. Five of 12 institutions had significantly longer waiting time from diagnosis to surgery (p<0.05). Trend analysis per quartile during covid period demonstrated that number of surgeries and timeliness dipped mainly in the first quartile, followed by rapid rebound in surgeries across all institutions in the next 2 quartiles. There was no difference in clinical stage at presentation in the 2 time periods. Conclusion: The COVID-19 pandemic initially impacted the number of breast cancer surgeries performed by institutions in Asia. This was followed by rapid adaptation and restoration of surgical services by institutions.